Asymptomatic colonization of Staphylococcus aureus with intermediate resistance to vancomycin harboring vanB resistance gene - HALA I AL-DAGHISTANI; Shquirat, Walid D; Al-kharabsha, Muna; Abd Al-latif, Saleh M (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Vancomycin has been used worldwide due to empirical therapy against methicillin-resistant Staphylococcus aureus infections. As a result a selective pressure that favors the outgrowth of vancomycin intermediate S. aureus clones will be created. This study was carried out to evaluate vancomycin resistance pattern of S. aureus in Jordan. Methods: A total of 1179 samples, including 566 (48%) from human and 613 (52%) from animals were examined for the presence of S. aureus using standard biochemical tests and polymerase chain reaction (PCR) amplification of coa gene. Resistance to antibiotics was determined by the disk diffusion method. Methicillin resistance strains were tested for vancomycin resistance by minimal inhibitory concentration (MIC), E- test, and the results were confirmed by amplification of van genes, and Pulsed-field gel electrophoresis (PFGE). Results: The prevalence of S. aureus among human source was: 19.35%, 14%, and 8.8% for nasal, nail, and skin, respectively, and for animal sources 27.3%, 5.51%, and 15.86% for milk, nasal, and meat, respectively. Four VISA strains (1.87%) were found to colonize human nares, nails, and skin with vancomycin MIC of 4-8 Î¼g/ml. Van B resistance gene was detected and PFGE with SmaI-digested VISA genomic DNA revealed two different pulsotypes. Conclusion: This is believed to be the first report of VISA strains containing vanB gene isolated from a routine carriage survey. Effective screening directed to persons colonized with VISA should therefore be a priority. Â 